Battista Botticelli, “maestro di legname” di Vasari - Cecchi, Alessandro (Opus Incertum, 2018)
The life and works of Battista di Bartolomeo Botticelli have remained to this day almost completely unknown. This article, thanks to new documentary research and a re-examination of Vasari’s sources, aims to shed light upon the career of a craftsman who executed the monumental carved platform ‘alla veneziana’ of the Salone dei Cinquecento, and was also Vasari’s trusted carpenter. He was already active in Rome in the 1550’s under the rule of Pope Julius III, where he constructed stages and friezes in the palaces belonging to the Pope and to Cardinal Ricci on Via Giulia. He was also active in Palazzo Vecchio, where he designed carved ceilings for the Quartiere di Eleonora and the platform of the Terrace of Saturn in the Quartiere degli Elementi, works which underline the central role played by Botticelli in Vasari’s fertile worksite, in a field such as the art of carpentry which still requires today new and in-depth research by scholars.